2019
DOI: 10.1088/1755-1315/278/1/012017
|View full text |Cite
|
Sign up to set email alerts
|

Using internal transcribed spacers 2 (ITS2) to identify seaweed species from Tomini Bay and Banten Bay

Abstract: Samples collected from two coastal areas by diving and using a boat. The fresh seaweed morphologically identified while the dried samples collected to be used for DNA testing. Previous research has been shown that there is an influence from environmental parameters on seaweed composition so that the water quality testing was carried out to determine the dominance of wild seaweed water. We conducted genomes extraction, PCR amplification, DNA sequencing testing, alignment with MEGA 7 application and made phyloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Moreover, studies have shown that molecular identification of Spirogyra can be determined through molecular biology approach using rbcL primer (Stancheva et al, 2013;Wongsawad and Peerapornpisal, 2014). The results of research from Dharmayanti et al (2018) submitted that the Internal Transcribed Spacers 2 (ITS2) DNA marker can be used for molecular identification of several types of algae collected from the Tomini Bay and Banten Bay in Indonesia.…”
Section: Various Dna Markers Used For Molecular Identification Of Seamentioning
confidence: 99%
“…Moreover, studies have shown that molecular identification of Spirogyra can be determined through molecular biology approach using rbcL primer (Stancheva et al, 2013;Wongsawad and Peerapornpisal, 2014). The results of research from Dharmayanti et al (2018) submitted that the Internal Transcribed Spacers 2 (ITS2) DNA marker can be used for molecular identification of several types of algae collected from the Tomini Bay and Banten Bay in Indonesia.…”
Section: Various Dna Markers Used For Molecular Identification Of Seamentioning
confidence: 99%